The Effects of Linguistic Qualifiers and Intensifiers on Group Interaction and Performance in Computer-Supported Collaborative Argumentation - Jeong, Allan C. (International Review of Research in Open and Distributed Learning, 2005)
This study tested the effects of linguistic qualifiers and intensifiers on the number and types of replies elicited per argument and per challenge posted in online debates. To facilitate collaborative argumentation, thirty-two students (22 females, 10 males) enrolled in a graduate-level online course classified and labeled their messages as arguments, challenges, supporting evidence, or explanations prior to posting each message. The findings showed that qualified arguments elicited 41 percent fewer replies (effect size = -.64), and the reduction in replies was greatest when qualified arguments were presented by females than males. Challenges without qualifiers, however, did not elicit more replies than challenges with qualifiers. These findings suggest that qualifiers were used to hedge arguments, and such behaviors should be discouraged during initial stages of identifying arguments (more so in all-female than in all-male groups) in order to elicit more diverse and more opposing viewpoints needed to thoroughly and critically analyze arguments.